Analysis of gene expression for microminipig liver transcriptomes using parallel long‐read technology and short‐read sequencing. (May 2016) - Sakai, Chizuka; Iwano, Shunsuke; Shimizu, Makiko; Onodera, Jun; Uchida, Masashi; Sakurada, Eri; Yamazaki, Yuri; Asaoka, Yoshiji; Imura, Naoko; Uno, Yasuhiro; Murayama, Norie; Hayashi, Ryoji; et al.
Abstract: The microminipig is one of the smallest minipigs that has emerged as a possible experimental animal model, because it shares many anatomical and/or physiological similarities with humans, including the coronary artery distribution in the heart, the digestive physiology, the kidney size and its structure, and so on. However, information on gene expression profiles, including those on drug‐metabolizing phase I and II enzymes, in the microminipig is limited. Therefore, the aim of the present study was to identify transcripts in microminipig livers and to determine gene expression profiles. De novo assembly and expression analyses of microminipig transcripts were conducted with liver samples from three male and three female microminipigs using parallel long‐read and short‐read sequencing technologies. After unique sequences had been automatically aligned by assembling software, the mean contig length of 50843 transcripts was 707 bp. The expression profiles of cytochrome P450 ( P450 ) 1A2, 2C, 2E1 and 3A genes in livers in microminipigs were similar to those in humans. Liver carboxylesterase ( CES ) precursor, liver CES‐like, UDP‐glucuronosyltransferase ( UGT ) 2C1‐like, amine sulfotransferase ( SULT )‐ like, N‐acetyltransferases ( NAT8 ) and glutathione S‐transferase ( GST ) A2 genes, which are relatively unknown genes in pigs and/or humans, were expressed strongly. Furthermore, no significant gender differences were observed in the gene expression profiles of phase I enzymes, whereas UGT2B17, SULT1E1, SULT2A1, amine SULT‐like, NAT8 and GSTT4 genes were different between males and females among phase II enzyme genes under the present sample conditions. These results provide a foundation for mechanistic studies and the use of microminipigs as model animals for drug development in the future. Copyright © 2016 John Wiley & Sons, Ltd.